Degradation of diiodoacetamide in water by UV/chlorination: Kinetics, efficiency, influence factors and toxicity evaluation. (February 2020) - Liu, Zhi; Lin, Yi-Li; Xu, Bin; Hu, Chen-Yan; Zhang, Tian-Yang; Cao, Tong-Cheng; Pan, Yang; Gao, Nai-Yun
Abstract: The formation and control of haloacetamides (HAcAms) in drinking water have raised high attention due to their high genotoxicity and cytotoxicity, especially the most cytotoxic one, diiodoacetamide (DIAcAm). In this study, the degradation of DIAcAm by UV/chlorination was investigated in terms of degradation kinetics, efficiency, influencing factors, oxidation products and toxicity evaluation. Results revealed that the degradation of DIAcAm by UV/chlorine process followed pseudo-first-order kinetics, and the rate constant between DIAcAm and OH radicals was determined as 2.8 × 10 9 M −1 s −1 . The contribution of Cl to DIAcAm degradation by UV/chlorine oxidation was negligible. Increasing chlorine dosage and decreasing pH significantly promoted the DIAcAm degradation during UV/chlorine oxidation, but the presence of bicarbonate (HCO3 − ) and natural organic matter (NOM) inhibited it. The mass balance analysis of iodine species was also evaluated during UV/chlorine oxidation of DIAcAm. In this process, with DIAcAm decreasing from 16.0 to 0.8 μM-I in 20 min, IO3 −, I − and HOI/I2 increased from 0 to 6.3, 6.1 and 0.5 μM-I, respectively. The increase of CHO cell viability during DIAcAm degradation indicated that the toxicity of DIAcAm could be decreased by chlorination, UV irradiation and UV/chlorine oxidation treatments, in which UV/chlorine oxidation was more effective on toxicity reduction than chlorination and UV irradiation alone. Graphical abstract: Image 1 Highlights: UV/chlorine is more effective on DIAcAm degradation than UV and chlorination alone. Kinetics models were established for DIAcAm degradation during UV/chlorine process. DIAcAm degradation by UV/chlorine is remarkably affected by pH, HCO3 − and NOM. IO3 −, I − and HOI/I2 can be produced during UV/chlorine oxidation of DIAcAm. DIAcAm toxicity can be reduced significantly by UV/chlorine oxidation.